2022
DOI: 10.3390/nu14193970
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alpha-Glycerylphosphorylcholine on Heart Rate Variability and Hemodynamic Variables Following Sprint Interval Exercise in Overweight and Obese Women

Abstract: The current study examined the effects of Alpha-Glycerylphosphorylcholine (A-GPC) on heart rate variability (HRV) and hemodynamic responses following a sprint interval exercise (SIE) in women who were overweight or obese. Participants (n = 12, 31.0 ± 4.6 years; 29.4 ± 2.1 kg/m2) consumed 1000 mg of A-GPC or a placebo after eating breakfast in a randomized, double-blind cross-over design. After 60 min, participants performed two bouts of the SIE (30 s Wingate) interspersed with 4 min of active recovery (40 rpm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Another study, by Barzanjeh et al [2], demonstrated the effects of alpha-glycerylphosphorylcholine (A-GPC), a food supplement, on heart rate variability (HRV) and hemodynamic responses following a sprint interval exercise in women with overweight or obesity. They hypothesized that the increased levels of free choline and acetylcholine that would result from consuming an alpha-glycerylphosphorylcholine supplement could play a protective role on cardiac autonomic and blood pressure in people with obesity when they are exposed to a bout of sprint interval exercise.…”
mentioning
confidence: 99%
“…Another study, by Barzanjeh et al [2], demonstrated the effects of alpha-glycerylphosphorylcholine (A-GPC), a food supplement, on heart rate variability (HRV) and hemodynamic responses following a sprint interval exercise in women with overweight or obesity. They hypothesized that the increased levels of free choline and acetylcholine that would result from consuming an alpha-glycerylphosphorylcholine supplement could play a protective role on cardiac autonomic and blood pressure in people with obesity when they are exposed to a bout of sprint interval exercise.…”
mentioning
confidence: 99%